Guidelines for Rational Cancer Therapeutics - Yoo, Byunghee; Billig, Ann-Marie; Medarova, Zdravka (Frontiers in Oncology, 2017)
Traditionally cancer therapy has relied on surgery, radiation therapy, and chemotherapy. In recent years, these interventions have become increasingly replaced or complemented by more targeted approaches that are informed by a deeper understanding of the underlying biology. Still, the implementation of fully rational patient-specific drug design appears to be years away. Here, we present a vision of rational drug design for cancer that is defined by two major components: modularity and image guidance. We suggest that modularity can be achieved by combining a nanocarrier and an oligonucleotide component into the therapeutic. Image-guidance can be incorporated into the nanocarrier component by labeling with a specific imaging reporter, such as a radionuclide or contrast agent for magnetic resonance imaging. While limited by the need for additional technological advancement in the areas of cancer biology, nanotechnology, and imaging, this vision for the future of cancer therapy can be used as a guide to future research endeavors.